Basic Challenges of Organizational Design and Organizational Structure as a Mediator to Organizational Performance: A Literature Review Study on Higher Education Institutions in DKI Jakarta - Leonardo, Michael Christianto; Zulman, Andry; Anggiani, Sarfilianty (Syntax Corporation, 2025)
This study explores the fundamental challenges of organizational design and their impact on organizational performance within higher education institutions in DKI Jakarta, with a specific focus on Universitas Bunda Mulia. Using a literature review approach, the research examines how organizational structure mediates the relationship between design challenges and performance outcomes. The study highlights that variations in organizational structures among universities significantly influence their performance, affecting factors such as decision-making efficiency, resource allocation, and adaptability to change. Key challenges identified include insufficient alignment between institutional goals and structure, resistance to change, and ineffective communication channels. The findings reveal that an optimized organizational design, tailored to the specific needs of the institution, can enhance operational efficiency and academic outcomes. This study also identifies the role of leadership in addressing these challenges and fostering a culture that supports continuous improvement. Recommendations include aligning the organizational structure with strategic objectives, investing in capacity-building programs, and promoting cross-functional collaboration to enhance adaptability and resilience. By addressing these challenges, educational institutions can improve their overall performance and better meet the demands of students, faculty, and stakeholders. This research contributes to the discourse on organizational design in higher education by providing practical insights and strategies for implementation.